Analisis Efisiensi Bank Umum Syariah dengan Metode Dea: Data Envelopment Analysis Periode 2021-2023 - Rosi Ariana Putri; Fitri Nur Latifah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the efficiency of Islamic Commercial Banks (BUS) in Indonesia during the 2021-2023 period using the Data Envelopment Analysis (DEA) method. Efficiency is measured based on the level of resource optimization by each bank in generating output. The results indicate fluctuations in the efficiency levels of BUS during the observation period. Some banks, such as BTPN Syariah and Bank Syariah Indonesia (BSI), demonstrated consistently high efficiency, while others, such as Bank Muamalat and BPD NTB Syariah, experienced either improvements or stagnation in efficiency. The key factors influencing efficiency include operational scale and assets, operational management strategies, technological innovation, and the post-pandemic impact. The implications of this study highlight the importance of strengthening risk management, investing in financial technology, and optimizing capital structure to enhance the efficiency of Islamic banking. By improving operational efficiency, Islamic banks can become more competitive and contribute significantly to the national financial system. Key words: Efficiency, Islamic Bank, Data Envelopment Analysis.